A realization of simple current-mode CMOS based true RMS-to-dc converter - Kaewdang, Khanittha; Kumwachara, Kiattisak; Surakampontorn, Wanlop (My University, 2004)
A simple circuit technique for the realization of an integrable current-mode CMOS true rms-to-dc converter is proposed. The realization scheme is based on the implicit computation method by makes use of the characteristic of a CMOS squaring circuit. Since the bias current of the circuit is provided by the IRMS, the conversion circuit consumes very low power. The performance of the circuit is studied through spectre in Cadence simulation results and experimental results. © 2004 IEEE.